Electronic Structure Engineering of Highly‐Scalable Earth‐Abundant Multi‐Synergized Electrocatalyst for Exceptional Overall Water Splitting in Neutral Medium. Issue 36 (11th November 2022) - Bahuguna, Gaurav; Cohen, Adam; Filanovsky, Boris; Patolsky, Fernando
Abstract: Efficient neutral water splitting may represent in future a sustainable solution to unconstrained energy requirements, but yet necessitates the development of innovative avenues for achieving the currently unmet required performances. Herein, a novel paradigm based on the combination of electronic structure engineering and surface morphology tuning of earth‐abundant 3D‐hierarchical binder‐free electrocatalysts is demonstrated, via a scalable single‐step thermal transformation of nickel substrates under sulfur environment. A temporal‐evolution of the resulting 3D‐nanostructured substrates is performed for the intentional enhancement of non‐abundant highly‐catalytic Ni 3+ and p Sn 2− species on the catalyst surface, concomitantly accompanied with densification of the hierarchical catalyst morphology. Remarkably, the finely engineered NiS x catalyst synthesized via thermal‐evolution for 24 h (NiS x ‐24 h) exhibits an exceptionally low cell voltage of 1.59 V (lower than Pt/C‐IrO2 catalytic couple) for neutral water splitting, which represents the lowest value ever reported. The enhanced performance of NiS x ‐24 h is a multi‐synergized consequence of the simultaneous enrichment of oxygen and hydrogen evolution reaction catalyzing species, accompanied by an optimum electrocatalytic surface area and intrinsic high conductivity. Overall, this innovative work opens a route to engineering the active material's electronic structure/morphology, demonstrating novel Ni 3+ / p Sn 2− ‐enriched NiS x catalysts which surpass state‐of‐the‐art materials for neutral water splitting. Abstract : Here, the simple and highly scalable preparation of earth‐abundant NiS x bi‐functional electrocatalyst exhibiting the best ever reported performance for neutral water splitting applications is presented. This remarkably enhanced performance is a multi‐synergized consequence of the method's capability to finely engineer the active material's surface electronic structure and morphology, thus surpassing the reported performance of state‐of‐the‐art materials for neutral water splitting.